Related Named Entities Classification in the Economic-Financial Context - De Los Reyes, Daniel (2021)
The present work uses the Bidirectional Encoder Representations from Transformers(BERT) to process a sentence and its entities and indicate whether two named entities present in a sentence are related or not, constituting a binary classification problem. It was developed for the Portuguese language, considering the financial domain and exploring deep linguistic representations to identify a relation between entities without using other lexical-semantic resources. The results of the experiments show an accuracy of 86% of the predictions.